Cauchy Problem for Nonuniformly Parabolic Equations with Degeneracy - Pukalskyi, I. D. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
In spaces of classical functions with power weight, we prove the existence and uniqueness of a solution of the Cauchy problem for nonuniformly parabolic equations without restrictions on the power order of degeneracy of the coefficients. We obtain an estimate for the solution of the problem in the corresponding spaces.